10-Hydroxydec-2-Enoic Acid Reduces Hydroxyl Free Radical-Induced Damage to Vascular Smooth Muscle Cells by Rescuing Protein and Energy Metabolism - Fan, Pei; Sha, Fangfang; Ma, Chuan; Wei, Qiaohong; Zhou, Yaqi; Shi, Jing; Fu, Jiaojiao; Zhang, Lu; Han, Bin; Li, Jianke (Frontiers in Nutrition, 2022)
10-Hydroxydec-2-enoic acid (10-HDA), an unsaturated hydroxyl fatty acid from the natural food royal jelly, can protect against cell and tissue damage, yet the underlying mechanisms are still unexplored. We hypothesized that the neutralization of the hydroxyl free radical (•OH), the most reactive oxygen species, is an important factor underlying the cytoprotective effect of 10-HDA. Here, we found that the •OH scavenging rate by 10-HDA (2%, g/mL) was more than 20%, which was achieved through a multiple step oxidization of the −OH group and C=C bond of 10-HDA. Moreover, 10-HDA significantly enhanced the viability of vascular smooth muscle cells (VSMCs) damaged by •OH (p < 0.01), significantly attenuated •OH-derived malondialdehyde production that represents cellular lipid peroxidation (p < 0.05), and significantly increased the glutathione level in •OH-stressed VSMCs (p < 0.05), indicating the role of 10-HDA in reducing •OH-induced cytotoxicity. Further proteomic analyses of VSMCs identified 195 proteins with decreased expression by •OH challenge that were upregulated by 10-HDA rescue and were primarily involved in protein synthesis (such as translation, protein transport, ribosome, and RNA binding) and energy metabolism (such as fatty acid degradation and glycolysis/gluconeogenesis). Taken together, these findings indicate that 10-HDA can effectively promote cell survival by antagonizing •OH-induced injury in VSMCs. To our best knowledge, our results provide the first concrete evidence that 10-HDA-scavenged •OH could be a potential pharmacological application for maintaining vascular health.